Tumour size is the only predictive factor of distant recurrence after pathological complete response to neoadjuvant chemotherapy in patients with large operable or locally advanced breast cancers: A sub-study of EORTC 10994/BIG 1-00 phase III trial. Issue 3 (February 2015) - Fei, F.; Messina, C.; Slaets, L.; Chakiba, C.; Cameron, D.; Bogaerts, J.; Bonnefoi, H.
Abstract Purpose Although achieving a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) in breast cancer predicts a better outcome, some patients still relapse. The objectives of this study were to describe the types of events in this group of patients and to identify predictive factors for relapse. Methods Patients with large operable or locally advanced breast cancers (T4d tumours were excluded) were randomised to receive either six cycles of anthracycline-based chemotherapy or three cycles of docetaxel followed by three cycles of eprirubicin/docetaxel. pCR was defined as no evidence of residual invasive cancer (or very few scattered tumour cells) in the primary tumour and axillary lymph nodes at surgery. Two Cox regression analyses were performed to identify predictive factors of relapse: one for recurrence-free interval (RFI) and one for distant recurrence-free interval (DRFI). Results Out of 283 eligible patients who achieved a pCR, 40 (14.1%) and 28 (9.9%) presented an event of interest for the RFI and DRFI analyses, respectively. Five-year RFI, DRFI and overall survival (OS) were 85.3% (95% confidence interval (CI), 80.1–89.3), 89.6% (95% CI, 85.0–92.9) and 91.9% (95% CI, 87.2–94.9), respectively. No predictors for RFI after pCR were identified. For DRFI, tumour size was the only predictor: Hazard ratio (HR) T3 versus T1–2 = 3.62 (95% CI, 1.66–7.89); HR T4 versus T1–2: HR, 2.80 (95% CI, 0.62–12.64) p = 0.0048. Conclusion In this study, clinical tumour size emerged as the only predictor for DRFI after pCR, with T3 and T4 tumours having an increased risk for distant recurrence compared to T1–2 tumours.